Temporal stability of tongue microbiota in older patients - A pilot study - Fa-Tzu Tsai; Cheng-Chieh Yang; Yu-Cheng Lin; Ming-Lun Hsu; Guang Hong; Mu-Chen Yang; Ding-Han Wang; Lin-Jack Huang; Chiu-Tzu Lin; Wun-Eng Hsu; Hsi-Feng Tu (Elsevier, 2024)
Background/purpose: Healthy states of human microbiota depend on a stable community of symbiotic microbes irrespective of external challenges from the environment. Thus, long-term stability of the oral microbiota is of importance, particularly for older patient populations. Materials and methods: We used next-generation sequencing (NGS) to examine the tongue microbiota of 18 individuals receiving long-term care over a 10-month period. Results: Beta diversity analysis demonstrated temporal stability of the tongue microbiota, as microbial compositions from all time points were indistinguishable from each other (P = 0.0887). However, significant individual variation in microbial composition (P = 0.0001) was observed, underscoring the presence of a unique microbial profile for each patient. Conclusion: The temporal dynamics of tongue microbiota exhibit long-term stability, providing diagnostic implications for oral diseases within older patient populations.